Emergency Abdominal Aortic Aneurysm Repair in a Patient with Failing Heart: Axillofemoral Bypass Using a Centrifugal Pump Combined with Levosimendan for Inotropic Support. (18th December 2011) - Michalek, Pavel; Sebesta, Pavel; Stern, Michael
Abstract : We describe the case of an 83-year-old patient requiring repair of a large symptomatic abdominal aortic aneurysm (AAA). The patient was known to have coronary artery disease (CAD) with symptoms and signs of significant myocardial dysfunction, left-heart failure, and severe aortic insufficiency. The procedure was performed with the help of both mechanical and pharmacological circulatory support. Distal perfusion was provided by an axillofemoral bypass with a centrifugal pump, with dobutamine and levosimendan administered as pharmacological inotropic support. The patient's hemodynamic status was monitored with continuous cardiac output monitoring and transesophageal echocardiography. No serious circulatory complications were recorded during the perioperative and postoperative periods. This paper suggests a potential novel approach to combined circulatory support in patients with heart failure, scheduled for open abdominal aortic aneurysm repair.